Effect of Oxymetholone by the Mother Treatment During Pregnancy and Lactation in the Testicular Tissue in Mature Male Rats - Mohammad Pourahmadi (Journal of Global Pharma Technology, 2017)
Introduction: Oxymetholone is an active nutritional anabolic - androgenic steroid which is used as a performance-enhancing drug in high dose and may result in the lung cancer, mineral deposits in the lungs, irregular cycles, ovarian and liver cancer. Unfortunately, some athletes take oxymetholone as a performance-enhancing drug for its anabolic effects and muscle growth in high doses. The aim of this study is to investigate oxymetholone induced complications in the testicular tissue in immature male rats, whose mothers were treated by oxymetholone during different pregnancy and lactation periods. Materials and Methods: In this study, we used fifty six female rats and fourteen male rats aged 110-120 days, weighing were approximately 200 ±20g. The animals were divided into groups including control, solvent 1 (pregnancy- 21 days), solvent 2 (pregnancy- lactation- 42days) solvent 3 (lactation - 21 days), experimental 1 (pregnancy 21 days) experimental 2 (pregnancy- lactation- 42 days), and experimental 3 (lactation-21 days). Solvent groups used DMSO with 99.5% concentration and experimental groups used oxymetholone with 10 mg/kg concentration by the intra peritoneum method. Results: The rate of spermatocyte cells in the experimental group of pregnancy-lactation and spermatid cells in the groups of pregnancy and pregnancy - lactation indicated a significant decrease compared to control. Conclusion: Oxymetholone in high doses or long-term influences on tissues and physiological activities in the reproductive system. Keywords: Oxymetholone, Spermatogenesis, Rats.